The Role Of Muhammad Yusof Bin Ahmad In The Development Of Malay Education, 1920 - 1950 - Abidin, Ahmad Husni Ahmad Zainal (2014)
This study examines the role of Muhammad Yusof bin Ahmad during a time when the social upward mobility of the Malay peasantry was dependent on Malay education and access to educational opportunities. Therefore, the objectives are; to analyze the development of Malay vernacular education in British Malaya from its inception to 1950; to discuss the emergence of the Malay Educational Service (MES) comprising a group of Malay administrators empowered to play a leading role; to employ a biographical approach to the study of Muhammad Yusof in constructing a historical biography with a special focus on his leadership attributes and dynamic relationship with British decision-makers; to evaluate Muhammad Yusof’s contribution to education development in Selangor, and British Malaya. To meet these objectives, Muhammad Yusof is weighed in as a focal point, with supporting data extracted from colonial records, curricula, Department of Education reports, and publications including surviving evidence from Muhammad Yusof’s archives. This is essential to consider what the Malay education development in British Malaya was all about; who the MES officials from 1920 to 1950 were, and their roles, responsibilities, and contributions to Malay education; who was Muhammad Yusof, and what was his role and contribution to Malay education. Lastly, it is on his work, influence, and impact as an education activist. For a methodology, a combination of qualitative method and a biographical approach is employed to discuss neglected areas in history and to reach a conclusion whereby there are two types of British officials whose action or inaction had a huge bearing on a given outcome. Equally important is the role of the MES, its Malay officials in general, and Muhammad Yusof in particular, to fill a gap in historical knowledge and to open the way to rethinking the colonial period. The broader implication of this study is that despite the inevitability of British domination, Muhammad Yusof had leveraged the constructive nature of British educationalists and navigated as an agent of change to advance the cause for Malay education and beyond.